Quiet eye and performance in sport: A meta-analysis - Lebeau, J. C.; Liu, S.; Sáenz-Moncaleano, C.; Sanduvete-Chaves, S.; Chacón-Moscoso, S.; Becker, B. J.; Tenenbaum, G. (Journal of Sport & Exercise Psychology, 2016)
Research linking the "quiet eye" (QE) period to subsequent performance has not been systematically synthesized. In this paper we review the literature on the link between the two through nonintervention (Synthesis 1) and intervention (Synthesis 2) studies. In the first synthesis, 27 studies with 38 effect sizes resulted in a large mean effect (d = 1.04) reflecting differences between experts` and novices` QE periods, and a moderate effect size (d = 0.58) comparing QE periods for successful and unsuccessful performances within individuals. Studies reporting QE duration as a percentage of the total time revealed a larger mean effect size than studies reporting an absolute duration (in milliseconds). The second synthesis of 9 articles revealed very large effect sizes for both the quiet-eye period (d = 1.53) and performance (d = 0.84). QE also showed some ability to predict performance effects across studies.